Effect of high-intensity interval training in patients with chronic hepatitis B and hepatic steatosis: A randomised controlled trial - Sofie Jespersen; Asmita Fritt-Rasmussen; Cody Garett Durrer; Eva Fallentin; Ellen Sloth Andersen; Peter Thielsen; Thomas Bandholm; Sten Madsbad; Bente Klarlund Pedersen; Christian Ritz; Nina Weis; Rikke Krogh-Madsen (PLoS ONE, 2026)
Background & aims Having both chronic hepatitis B and hepatic steatosis increases the risk of liver-related morbidity and mortality. We aimed to investigate if high-intensity interval training could decrease the liver fat-fraction and improve liver status, body composition, lipid- and glucose metabolism, and blood pressure in patients with chronic hepatitis B and hepatic steatosis. Methods In a randomised, controlled trial, patients with chronic hepatitis B and hepatic steatosis were randomised 1:1 to high-intensity interval training over 12 weeks or no intervention. The primary outcome was reduction in liver fat-fraction (≥ 2.8%), assessed by magnetic resonance imaging. Secondary outcomes were body composition, indices of glucose metabolism, blood lipids, blood pressure, alanine aminotransferase, physical fitness assessed by maximal oxygen consumption (VO 2 max), and self-assessed health. The trial was discontinued before reaching the planned sample size due to slow recruitment. Results Nineteen patients were included, and 14 completed the trial (seven per group). Changes in liver fat-fraction showed a between-group difference of −2.03% [95% CI: −5.5 to 1.4; p = 0.22]. Exercising patients improved VO 2 max by 5.6 mL/kg/min [1.7 to 9.5; p < 0.05] and emotional well-being by 18.07 points [6.6 to 29.6; p < 0.05]. The exercise intervention did not affect total body fat −0.35% [−2.8 to 2.1] or lean body mass 0.6 kg [−0.7 to 1.9]. Changes in glucose tolerance, insulin secretion, Matsuda index −0.89 [−2.5 to 0.5; p = 0.18], cholesterol 0.29 mmol/L [−0.3 to 0.9; p = 0.32] and systolic blood pressure 6.36 mmHg [−6.4 to 19.1; p = 0.29] did not differ significantly between groups. Conclusions We did not observe a significant effect of high-intensity interval training on liver fat-fraction in patients with chronic hepatitis B and hepatic steatosis. Due to premature discontinuation and the resulting limited sample size, the study was underpowered, and the findings should be interpreted as exploratory. Nevertheless, the intervention improved physical fitness and emotional well-being.